Stay at Mosque: Congregational Worship, Covid-19 Pandemic and Islamic Living Law in West Sumatra. (Mazahib, 2022)
Abstract The article explains people’s argumentation in Minangkabau, who decided to continue worshiping at mosques during the COVID-19 pandemic. The data shown in this article were acquired through in-depth interviews with six sources: ulama, traditional-cultural figures, and mosque caretakers who continue to hold congregational prayers during the pandemic. The study found that the religious-cultural identity inherent in Minangkabau people serves as a driving factor for them to keep on praying in mosques during the pandemic. These congregational worshiping activities in mosques during the pandemic had subsequently become more widespread as the government had not monitored them. This condition indicates that government or state policy on Covid 19 pandemic is negotiable with the religious culture of the Minangkabau people. This article may have implications for studies concerning Islamic laws relating to worship in the socio-cultural context during health emergencies and new relations between the ulama (Islamic scholars), government, and traditional-cultural-religious figures. Keywords: Mosque-Surau, COVID-19 pandemic, Minangkabau, Ulama